Enforcement of Consumer Rights Through Dispute Settlement Resolution Agency to Improve the Consumer Satisfaction Index In Indonesia - Subagyono, Bambang Sugeng Ariadi; Chumaida , Zahry Vandawati; Romadhona, Mochamad Kevin (Yuridika, 2022)
Legal protection of consumer rights in essence is the role of the government to protect the interests of consumers in the framework of trade. Violation of consumer protection norms can only be enforced if business actors are willing to voluntarily fulfill consumer demands for the fulfillment of consumer rights that have been violated by business actors. However, if the business actor is not willing to carry it out voluntarily, while the consumer assumes that the business actor concerned has violated the consumer protection norms stipulated by the UUPK and is detrimental to the consumer, then the enforcement of the consumer protection norms can only be prosecuted through a dispute specified resolution process in the UUPK. The purpose of establishing the Consumer Dispute Settlement Agency (BPSK) is to protect consumers and business actors by creating a consumer protection system that contains elements of legal certainty and information disclosure. This study is to analyze the implementation of consumer rights enforcement through the Consumer Dispute Resolution Board in order to increase the consumer satisfaction index, as well as to analyze the obstacles and barriers to consumer rights enforcement through the Consumer Dispute Resolution Board.